Gamification and Purchase Intention on E-commerce Platforms: The Mediating Role of User Engagement and Moderating Role of Gender - Bimewahqi Najmi; Titik Rosnani; Ana Fitriana; Ramadania; Wenny Pebrianti (Al-Qalam Institue, 2026)
The e-commerce industry continues to show significant growth, accompanied by increasingly intense competition among platforms. However, some platforms face challenges such as declining traffic and user engagement, despite maintaining a large market share. This study aims to analyze the effect of gamification on purchase intention, with user engagement as a mediating variable and gender as a moderating variable. The research employs a quantitative approach through an online survey of users engaging with gamification features on e-commerce platforms. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0. The results indicate that gamification has a positive and significant effect on user engagement but a negative and significant effect on purchase intention. User engagement has a very strong positive effect on purchase intention and is proven to mediate the relationship between gamification and purchase intention. Meanwhile, gender was not found to moderate this relationship. These findings underscore the importance of user engagement as a key factor driving consumer purchase intention. The study’s implications suggest that platform managers should develop gamification strategies that create meaningful engagement integrated with transactional activities to enhance users’ purchase intention.